UNIT 11A.3 Chlamydia trachomatis Transformation and Allelic Exchange Mutagenesis. Issue 1 (16th May 2017) - Mueller, Konrad E.; Wolf, Katerina; Fields, Kenneth A.
Abstract : Gene inactivation is essential for forward and reverse genetic approaches to establish protein function. Techniques such as insertion or chemical mutagenesis have been developed to mutagenize chlamydiae via targeted or random mutagenesis, respectively. Both of these approaches require transformation of chlamydiae to either introduce insertion elements or complement mutants. We have recently developed a targeted mutagenesis strategy, f luorescence‐r eported a llelic e xchange m utagenesis (FRAEM), to delete Chlamydia trachomatis L2 genes. This approach overcomes several barriers for genetically manipulating intracellular bacteria. Perhaps most significantly, FRAEM employs fluorescence reporting to indicate successful transformation and subsequent recombination events. Three protocols are provided that detail methods to construct gene‐specific suicide vectors, transform C. trachomatis L2 to select for recombinants, and isolate clonal populations via limiting dilution. In aggregate, these protocols will allow investigators to engineer C. trachomatis L2 strains carrying complete deletions of desired gene(s). © 2017 by John Wiley & Sons, Inc.